2011
DOI: 10.1016/j.neuro.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Mn/Zn ethylene-bis-dithiocarbamate and glyphosate pesticides leads to neurodegeneration in Caenorhabditis elegans

Abstract: Epidemiological evidence suggests positive correlations between pesticide usage and the incidence of Parkinson's disease (PD). To further explore this relationship, we used wild type (N2) Caenorhabditis elegans (C. elegans) to test the following hypothesis: Exposure to a glyphosate-containing herbicide (TD) and/or a manganese/zinc ethylene-bis-dithiocarbamate-containing fungicide (MZ) may lead to neurotoxicity. We exposed N2 worms to varying concentrations of TD or MZ for 30 min (acute) or 24 hours (chronic). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 45 publications
2
55
2
Order By: Relevance
“…Impaired dopaminergic signaling in the substantia nigra is a key feature of Parkinson's disease, and Parkinson's risk has been associated with exposure to various pesticides, including the herbicide paraquat [238], although, to our knowledge, glyphosate has not yet been studied in this respect. However, exposure of C. elegans to glyphosate led to pathology in the nervous system in the region analogous to the nigrostriatal dopamine system associated with Parkinson's disease [239].…”
Section: Dopamine and Parkinson's Diseasementioning
confidence: 99%
“…Impaired dopaminergic signaling in the substantia nigra is a key feature of Parkinson's disease, and Parkinson's risk has been associated with exposure to various pesticides, including the herbicide paraquat [238], although, to our knowledge, glyphosate has not yet been studied in this respect. However, exposure of C. elegans to glyphosate led to pathology in the nervous system in the region analogous to the nigrostriatal dopamine system associated with Parkinson's disease [239].…”
Section: Dopamine and Parkinson's Diseasementioning
confidence: 99%
“…Oxidative stress also resulted in the neurodegeneration of dopaminergic (DAergic) neurons, indicated by the fact that treated worms showed a significant decrease in DA concentration compared to untreated worms [143]. Similar neurodegeneration has been shown following exposure to mancozeb [144,145].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 66%
“…Manganese-containing dithiocarbamate fungicides, such as maneb and mancozeb, have been researched heavily due to their neurotoxicity [143][144][145]. Manganese exposure by itself has been shown to result in a variety of detrimental effects in C. elegans [146][147][148].…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 99%
“…This aspect reinforces the concept that there must be other substances or chemicals in the water samples that were not detected a priori but even so exert weighty toxicological effects. Several reports showed that C. elegans was sensitive to different substances such as pesticides, heavy metals and toxins (Höss et al, 2013;Jiang et al, 2016;Lewis et al, 2013;Negga et al, 2011;Ruan et al, 2009;Yunhui et al, 2009). So it is possible that C. elegans toxicity could be explained by pollutants derived from the anthropogenic activities developed in the area (like agriculture, livestock and recreations).…”
Section: Multivariate Linear Model and Simple Regression Of Relative mentioning
confidence: 99%